2012
DOI: 10.1016/s2255-4971(15)30005-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Complications of Surgical Treatment of Fractures of the Proximal Extremity of the Humerus Using a Locking Plate

Abstract: Objective: To evaluate the complications from surgical treatment using a locking plate among patients with fractures of the proximal extremity of the humerus. Methods: Between July 2004 and December 2009, 56 patients with fractures of the proximal extremity of the humerus were treated using the PHILOS® plate. There were 19 male patients and 37 female patients, with a mean age of 62 years (range: 30 to 92 years). All the cases had a mean postoperative followup period of 12 months. Thirteen fractures were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…In our study, total of 7 patients out of 32 had complications (21.8%). In literature, the reported complication rates are ranging from 3.7% to 35.7% [9,11,12] The main complication in our study was inadequate reduction of the fracture ( Fig. 1).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In our study, total of 7 patients out of 32 had complications (21.8%). In literature, the reported complication rates are ranging from 3.7% to 35.7% [9,11,12] The main complication in our study was inadequate reduction of the fracture ( Fig. 1).…”
Section: Discussionmentioning
confidence: 56%
“…We had one case (3.2%) which was fixed in varus position and healed with malunion. Miyazaki et al [9] reported that 3.3% of their cases developed this complication. Varus malposition is defined as a head shaft angle of less than 120 degrees.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The greater number of complications were associated with incorrect surgical technique, with 40% of complications already presented at the end of the procedure. 9 …”
Section: Discussionmentioning
confidence: 99%